PERANAN KEJAKSAAN TERHADAP PEMBERANTASAN KORUPSI DI KALIMANTAN TIMUR - Khairunnisah, Khairunnisah (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
This research is held in Samarinda in 2017 either observation, spreading questionairs or reading the TribunKaltim Daily newspaper.The method is qualitative research.The population is the local goverments of East Kalimantan which consists of 10 (ten) places of courtsnamelyBerau, East Kutai,Bontang, Balikpapan, Paser, Panajam Paser Utara,Samarinda,Kutai Kartanegara, Kutai Barat and Mahulu.The samples are Samarinda,Bontang and Kutai Barat about 30 %.The results of the research are (1). Almost in November 2017,the supervisons of the corruption extraordinary crimes listed 46 data,(2).The state money have been saved in 2017 reaching Â Rp.13 billion rupiahs,(3).Corruption in Bontang on the project of saving beach at Beras Basah in the budget of 2013 to 2015,(4).Landown Bank of Samarinda local government 2004-2006,(5).The budget of health tools,(5).The social fund for the Cendana Skill Course Service,(6).The education aid and healths tools funds in Kutai Barat.The suggestions given by the researher are (1).The society has to be brave to report to the officer concerned if there is any corruption crime deed, (2).It is better to prevent it rather than to sentence the corruptors,(3).The internal and external control have to be accomplished,(4).The managements of the funds of the project and state have to be transparant,(5).The persons who report it have to be appreciated,(6).The apparatus and contractors those who are honest to doÂ  the projects have to be appreciated, (7).The corruptors have to be sentenced heavily.